Structural basis for adaptation of lactobacilli to gastrointestinal mucus - Etzold, Sabrina; Kober, Olivia I.; MacKenzie, Donald A.; Tailford, Louise E.; Gunning, A. Patrick; Walshaw, John; Hemmings, Andrew M.; Juge, Nathalie (Environmental microbiology, 2014)
Summary The mucus layer covering the gastrointestinal (GI) epithelium is critical in selecting and maintaining homeostatic interactions with our gut bacteria. However, the underpinning mechanisms of these interactions are not understood. Here, we provide structural and functional insights into the canonical mucus‐binding protein (MUB), a multi‐repeat cell‐surface adhesin found in Lactobacillus inhabitants of the GI tract. X‐ray crystallography together with small‐angle X‐ray scattering demonstrated a ‘beads on a string’ arrangement of repeats, generating 174 nm long protein fibrils, as shown by atomic force microscopy. Each repeat consists of tandemly arranged Ig‐ and mucin‐binding protein (MucBP) modules. The binding of full‐length MUB was confined to mucus via multiple interactions involving terminal sialylated mucin glycans. While individual MUB domains showed structural similarity to fimbrial proteins from Gram‐positive pathogens, the particular organization of MUB provides a structural explanation for the mechanisms in which lactobacilli have adapted to their host niche by maximizing interactions with the mucus receptors, potentiating the retention of bacteria within the mucus layer. Together, this study reveals functional and structural features which may affect tropism of microbes across mucus and along the GI tract, providing unique insights into the mechanisms adopted by commensals and probiotics to adapt to the mucosal environment.